Zom-B family - Shan, Darren (Shan, Darren. Zom-B (Series), 2014)
"Now a prisoner of the most heinous survivors of the human race, B finds herself at the mercy of her enemies and discovers the fate of her parents and friend Vinyl, calling into question how much she is willing to sacrifice in the name of justice"--